STRENGTHENING STUDENTS’ SOCIO-CULTURAL LITERACY IN MADRASAH WITH AKMI (CASE STUDY OF PRIVATE MI IN KUDUS REGENCY) - Zarkasi Zarkasi; Ghozali Ghozali (2024)
This study aims to explore how to strengthen the socio-cultural literacy of students in madrasas through the implementation of the Indonesian Madrasah Competency Assessment (AKMI). Socio-cultural literacy is the ability to understand and interact with the culture and society around us, socio-cultural literacy is one of the differentiators from literacy developed by the Ministry of Education and Culture through the Minimum Competency Assessment (AKM). Through a qualitative method with a case study approach, this study analyzes how AKMI can be used as a tool to improve students' socio-cultural literacy in Private MI Kudus Regency. The results of the study show that AKMI is not only able to measure academic competence but can also encourage better socio-cultural understanding among madrasah students by increasing teacher training, resource support, and community involvement. Thus, it is hoped that the students will become agents of socio-cultural literacy in their respective communities when they are at home.